Exploring the Relationship Between Education and Obesity - Devaux, Marion (OECD Publishing, 2011)
An epidemic of obesity has been developing in virtually all OECD countries over the last 30 years. Existing evidence provides a strong suggestion that such an epidemic has affected certain social groups more than others. In particular, a better education appears to be associated with a lower likelihood of obesity, especially among women. This paper sheds light on the nature and the strength of the correlation between education and obesity. Analyses of health survey data from Australia, Canada, England, and Korea were undertaken with the aim of exploring this relationship. Social gradients in obesity were assessed across the entire education spectrum, overall and in different population sub-groups. Furthermore, investigations testing for mediation effects and for the causal nature of the links observed were undertaken to better understand the underlying mechanisms of the relationship between education and obesity
Keywords: Economics